Moodle-based E-Learning Model for Critical Thinking in the Lesson of Electromagnetic Induction - Ketang Wiyono; Zulherman Zulherman; Saparini Saparini; Melly Ariska; Rini Khoirunnisa; Sri Zakiyah (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2020)
This study aims to develop a valid and practical e-learning model for critical thinking skills using the moodle platform in the lesson of electromagnetic induction. Dick and Carey instructional design model is applied for the product development—which consists of nine stages, (1) instructional goals identification, (2) instructional analysis, (3) learners and contexts analysis, (4) objective performance arrangement, (5) assessment instruments development, (6) instructional strategy’s plan, (7) instructional material selection, (8) preparation for conducting a formative evaluation of the instruction, and (9) revise instruction. The results reveal the moodle design is valid and practical regarding expert and user perspectives, respectively. Besides, there is an improvement of student’s critical thinking skills according to the obtained n-gain score, which stands for 0.38.